Pore-Scale Oil-Water Flow Behaviors in Different Development Adjustment Schemes for Enhancing Oil Recovery in Waterflooding - Jianjun Du; Tao Xue; Tao Ning; Bingtao Hu; Jinbiao Yu; Chen Wang (Geofluids)
Development mode adjustment is an important measure to further enhance oil recovery after primary waterflooding. Investigating the oil-water flow behaviors in the pores is significant to deepening the understanding of the macrobehavior of waterflooding and the designation of the reservoir development plan. Previous studies mainly focused on the change in recovery factor and macroflow characteristics, while less attention was paid to the causes of the change in recovery factor and the difference in macrocharacteristics. In this paper, the numerical simulation technology by coupling the Navier-Stokes equation with the method of volume of fluid is employed to investigate the dynamic formation mechanism of the remaining oil at pore-scale in the primary waterflooding, and then the pore-scale oil-water two-phase behaviors under three waterflooding development adjustment schemes: changing flooding direction, turning extraction well to injection well, and increasing injection rate are studied. The research shows that when the viscous resistance of the water-bearing channel is less than the sum of the capillary barrier and drainage capillary resistance (the resistance in the displacement of wetting phase displacement using the nonwetting phase), the remaining oil is formed. Water➔oil➔water➔oil displacement mode is formed in the process of changing flow direction, which makes the force of the phase interface tend to balance, reduces the capillary effect in waterflooding, and improves oil recovery. In the process of developing the scheme of turning extraction into an injection well, through multipoint injection, it advances from the central water-bearing area to the oil-bearing area on both sides in multiple paths, forming a larger spatial spread range than that in the change of flooding direction. Under the influence of the capillary barrier effect and drainage capillary resistance, when the injection rate is increased, the remaining oil can restart to move only when the flowing rate exceeds a certain value. The small viscous resistance in the water-bearing channel and the lateral resistance from the capillary barrier limiting the lateral sweep of water are the primary reasons for the insignificant improvement of oil recovery under the condition of a low liquid injection rate. The findings of this study can help for better understanding of pore-scale flow mechanism behaviors and their influences on the macroscopic development features in the waterflooding process.